Composite Biphase Coatings Formed by Hybrid Technology for Biomedical Applications; Energy Fluxes and Radiation Effects (EFRE-2020 online) - Vorobiev A. V. Aleksandr Vladimirovich; Fedotkin A. Yu. Aleksandr Yurjevich; Kozelskaya A. I. Anna Ivanovna; Korotchenko N. Natalia; Gigilev A. Alexander; Shesterikov E. Evgeny; Tverdokhlebov S. I. Sergei Ivanovich (2020, 2020)
Title screen